Developing StoryCarnival: exploring computer-mediated activities for 3 to 4 year-old children - Pantoja, Luiza Superti Pantoja; Hourcade, Juan Pablo Hourcade; Diederich, Kyle Diederich; Crawford, Liam Crawford; Utter, Victoria Utter (Teste, 2019)
Many children begin Kindergarten without important skills such as the ability to pay attention, to follow instructions, and to wait for their turn. There is evidence that some of these deficits are associated to poor self-regulation, which relates to the ability of controlling attention and emotion in order to complete an action. Based on the activities promoted by the Tools of the Mind curriculum, we have been iteratively developing StoryCarnival, a web app designed to support make-believe play for three to four year-old children with the goal of improving selfregulation. This short paper briefly discusses our approach and some related work, the design sessions that informed the development of our prototypes, and some lessons learned while collaborating with young children.